In vivo studies of the PARP inhibitor, AZD-2281, in combination with fractionated radiotherapy: An exploration of the therapeutic ratio. Issue 3 (September 2015) - Gani, Cihan; Coackley, Carla; Kumareswaran, Ramya; Schütze, Christina; Krause, Mechthild; Zafarana, Gaetano; Bristow, Robert G.
Abstract Background and purpose Pre-clinical data have shown that PARP inhibitors (PARPi) may increase the efficacy of radiotherapy in prostate cancer. However, it is uncertain as to whether PARPi lead to clonogenic kill when combined with radiotherapy (RT). Material and methods We tested the PARP inhibitor AZD-2281 as a radiosensitizing agent under oxic and hypoxic conditions for clonogenic survival in vitro and in vivo using the human prostate cancer cell line, 22Rv1. In addition, the effects of PARPi + RT on normal tissue were investigated using a crypt clonogenic assay. Results AZD-2281 inhibited cellular PARP activity under both oxic and hypoxic conditions. The addition of AZD-2281 radiosensitized 22Rv1 cells under oxia, acute hypoxia and chronic hypoxia in vitro. The combination of AZD-2281 with fractionated radiotherapy resulted in a significant growth delay and clonogenic kill in vivo. No increased gut toxicity was observed using this combined PARPi + radiotherapy regimen. Conclusions This is the first preclinical study to demonstrate direct clonogenic kill in vivo by the addition of AZD-2281 to radiotherapy. As we did not observe gut toxicity, the use of PARPi in the context of prostate cancer radiotherapy warrants further investigation in clinical trials.